Mapping Canada’s Indigenous Digital Collections - Shiri, Ali; Borys, Christina; Huang, Carolin (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2019)
The objective of this paper is to report on a comprehensive study to examine, identify, and map Canada’s Indigenous digital collections available on the web in order to provide a metadata-rich, map-based interface that supports unified, organized, and systematic access to the Indigenous digital collections.